The Effectiveness of Early Childhood Nutrition Health Education on Reducing the Incidence of Stunting - Ellyzabeth Sukmawati; Kartini Marzuki; Ardiana Batubara; Nur Afifah Harahap; Efendi Efendi; Pius Weraman (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to assess the effectiveness of early childhood nutrition health education in reducing stunting prevalence. The research utilized a literature review approach, analyzing various relevant sources. The findings indicate that nutrition health education during early childhood provides significant advantages in addressing stunting. Targeting parents and caregivers, implementing healthy feeding programs, and providing practical training in preparing nutritious food have been successful in improving children's nutritional status and decreasing the risk of stunting. This research offers a comprehensive understanding of the importance of early childhood nutrition health education as a stunting prevention strategy. The results emphasize the need for a holistic and integrated approach that considers social and economic factors to address stunting. Collaborative efforts among stakeholders are crucial in reducing stunting incidence